Combined Thermodynamic and Kinetic Models for Processing of Materials - Gunnar Eriksson (The Minerals, Metals and Materials Society, 2001)
Computer simulation has become an everyday practice in thennodynamic and materials research. Advanced thennochemical algorithms take into account heat transfer effects and salient reaction kinetics when applied for process models. In particular, the combination of mass transfer or overall reaction rates with multi-component Gibbs energy minimisation provides an effective tool for simulation of industrial thennochemical processes and processing of materials. In this work the combination of rate factors with the Gibbs energy technique was studied by using the novel program ChemSheet, which operates through Microsoft's Excel® spreadsheets. Such processes as, for example, CVD of pure silicon production, titania pigment manufacturing, vapour pressure of Mercury in amalgams (in Hg-Iamp manufacturing) and melting behaviour of low-temperature alloys have been modelled. Provided that the thennochemical data is available simulations can be performed with any thennodynamic system. The calculation can be performed as an affinity study without a particular reactor model or with a specific reactor scheme.